Could nanotechnology improve exercise performance? Evidence from animal studies - M.R. Lima; B.J. Moreira; R. Bertuzzi; A.E. Lima-Silva (Brazilian Journal of Medical and Biological Research, 2024)
Abstract This review provides the current state of knowledge regarding the use of nutritional nanocompounds on exercise performance. The reviewed studies used the following nanocompounds: resveratrol-loaded lipid nanoparticles, folic acid into layered hydroxide nanoparticle, redox-active nanoparticles with nitroxide radicals, and iron into liposomes. Most of these nutritional nanocompounds seem to improve performance in endurance exercise compared to the active compound in the non-nanoencapsulated form and/or placebo. Nutritional nanocompounds also induced the following physiological and metabolic alterations: 1) improved antioxidant activity and reduced oxidative stress; 2) reduction in inflammation status; 3) maintenance of muscle integrity; 4) improvement in mitochondrial function and quality; 5) enhanced glucose levels during exercise; 6) higher muscle and hepatic glycogen levels; and 7) increased serum and liver iron content. However, all the reviewed studies were conducted in animals (mice and rats). In conclusion, nutritional nanocompounds are a promising approach to improving exercise performance. As the studies using nutritional nanocompounds were all conducted in animals, further studies in humans are necessary to better understand the application of nutritional nanocompounds in sport and exercise science.